P162 When Do Patients with Known Lung Cancer Present to Emergency Services?. (19th November 2012) - Joshi, P; Berry, MPR; Bowen, F
Abstract : Introduction: Use of electronic patient alerts systems are encouraged by government initiatives, especially within the realms of oncology, as a way of expediting relevant clinical review of oncology patients. When a known cancer patient attends an emergency unit, an electronic alert advises selected clinical team members of the attendance, to allow rapid assessment and appropriate management in line with patient's stage of malignancy. Methods: Retrospective data captured by the electronic patient alert system was analysed. Data was from three hospital sites within the same trust, which are together form a tertiary referral centre. Data from March 2010 till April 2012 was included. Results: There were 15, 625 cancer attendances in total over the time period, 1, 684 were for patients with lung cancer (10.8%). There was no detectable seasonal variation in any cancer group. 1341 of the total cancer admissions occurred during weekdays, averaging 268 patients per named day (12–17% each day) with a fall to approximately 10% at weekends (166 and 177 on Saturdays and Sundays respectively). Overall for lung cancer, 46% (781/1684) of emergency admissions are in-hours (defined Monday to Friday, 9am to 5pm), compared to 42% (6619/15625) of all cancer presentations. Over the whole week, 13% (217/1684) of lung cancer patients arrived before 9am (between midnight and 9am), and 30% (509/1684) arrive after 5 (between 5pm and midnight). Approximately a quarter (24%= 410/1684) of emergency lung cancer attendances occurred between 5pm on Friday and 9am on Monday. Conclusion. This information would indicate that a substantial proportion of unscheduled lung cancer work occurs out-of-hours. To optimise patient care and prevent attendances there may be justification for exploring alternative ways of working to improve cover in late afternoon and early evening when there is increased patient attendance so that these alerts can be received and acted upon rapidly. These data suggest that increased community support is needed especially at weekends.